Aoypmata : critical essays on the archaeology of the Eastern Mediterranean in honour of E. Susan Sherratt - Sherratt, Susan; Galanakis, Ioannis, 1979-; Wilkinson, Toby, 1969-; Bennet, John, 1957- (Archaeopress archaeology., 2014)
Over her career Susan Sherratt has questioned our basic assumptions in many areas of the later prehistory of the Mediterranean and Europe, deploying a canny eye for detail, but never losing sight of the big picture. Her collected works include contributions on the relationship between Homeric epic and archaeology; the economy of ceramics, metals and other materials; the status of the `Sea Peoples' and other ethnic terminologies; routes and different forms of interaction; and the history of museums/collecting (especially relating to Sir Arthur Evans). The editors of this volume have brought together a cast of 32 scholars from nine different countries who have contributed these 26 papers to mark Sue's 65th birthday.